Three-dimensional structural optimization of a cementless hip stem using a bi-directional evolutionary method. Issue 1 (2nd January 2020) - Rahchamani, Reza; Soheilifard, Reza
Abstract: A correct choice of stem geometry can increase the lifetime of hip implant in a total hip arthroplasty. This study presents a numerical methodology for structural optimization of stem geometry using a bi-directional evolutionary structural optimization method. The optimization problem was formulated with the objective of minimizing the stresses in the bone–stem interface. Finite element analysis was used to obtain stress distributions by three-dimensional simulation of the implant and the surrounding bone under normal walking conditions. To compare the initial and the optimal stems, the von Mises stress distribution in the bone–implant interface was investigated. Results showed that the optimization procedure leads to a decrease in the stress concentration in the implant and a reduction in stress shielding of the surrounding bone. Furthermore, periprosthetic bone adaptation was analyzed numerically using an adaptive bone remodeling procedure. The remodeling results showed that the bone mass loss could be reduced by 16% in the optimal implant compared to the initial one.